2017
DOI: 10.1093/cercor/bhx186
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Parietal Cortex to the Working Memory of an Obstacle Acquired Visually or Tactilely in the Locomoting Cat

Abstract: A working memory of obstacles is essential for navigating complex, cluttered terrain. In quadrupeds, it has been proposed that parietal cortical areas related to movement planning and working memory may be important for guiding the hindlegs over an obstacle previously cleared by the forelegs. To test this hypothesis, parietal areas 5 and 7 were reversibly deactivated in walking cats. The working memory of an obstacle was assessed in both a visually dependent and tactilely dependent paradigm. Reversible bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…However, neurons exhibiting sustained delay period modulation represent a specialized subset of area 5 neurons capable of maintaining stable representations of obstacle infor-mation in WM. As previous work demonstrated WM deficits precluding successful avoidance when a comparable region of area 5 was deactivated [9,10,28], neurons capable of stable WM maintenance are most likely necessary for such behaviors.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…However, neurons exhibiting sustained delay period modulation represent a specialized subset of area 5 neurons capable of maintaining stable representations of obstacle infor-mation in WM. As previous work demonstrated WM deficits precluding successful avoidance when a comparable region of area 5 was deactivated [9,10,28], neurons capable of stable WM maintenance are most likely necessary for such behaviors.…”
Section: Discussionmentioning
confidence: 87%
“…During this time, the obstacle was covertly removed from the walkway before locomotion resumed. In comparison to obstacle-absent trials (OA), elevated hindleg stepping observed during OP continuation demonstrated the ability of animals to remember the obstacle over which the forelegs stepped ( Figure 1B) [4,8,9].…”
Section: Modulated Ppc Activity During Wm-guided Obstacle Negotiationmentioning
confidence: 98%
See 3 more Smart Citations